Cost-effectiveness of a Medical Care Coordination Program for People With HIV in Los Angeles County. (16th December 2019) - Flash, Moses J E; Garland, Wendy H; Martey, Emily B; Schackman, Bruce R; Oksuzyan, Sona; Scott, Justine A; Jeng, Philip J; Rubio, Marisol; Losina, Elena; Freedberg, Kenneth A; Kulkarni, Sonali P; Hyle, Emily P
Abstract: Background: The Los Angeles County (LAC) Division of HIV and STD Programs implemented a medical care coordination (MCC) program to address the medical and psychosocial service needs of people with HIV (PWH) at risk for poor health outcomes. Methods: Our objective was to evaluate the impact and cost-effectiveness of the MCC program. Using the CEPAC-US model populated with clinical characteristics and costs observed from the MCC program, we projected lifetime clinical and economic outcomes for a cohort of high-risk PWH under 2 strategies: (1) No MCC and (2) a 2-year MCC program. The cohort was stratified by acuity using social and clinical characteristics. Baseline viral suppression was 33% in both strategies; 2-year suppression was 33% with No MCC and 57% with MCC. The program cost $2700/person/year. Model outcomes included quality-adjusted life expectancy, lifetime medical costs, and cost-effectiveness. The cost-effectiveness threshold for the incremental cost-effectiveness ratio (ICER) was $100 000/quality-adjusted life-year (QALY). Results: With MCC, life expectancy increased from 10.07 to 10.94 QALYs, and costs increased from $311 300 to $335 100 compared with No MCC (ICER, $27 400/QALY). ICERs for high/severe, moderate, and low acuity were $30 500/QALY, $25 200/QALY, and $77 400/QALY. In sensitivity analysis, MCC remained cost-effective if 2-year viral suppression was ≥39% even if MCC costs increased 3-fold. Conclusions: The LAC MCC program improved survival and was cost-effective. Similar programs should be considered in other settings to improve outcomes for high-risk PWH.